APLIKASI UNTUK INFORMASI PENJUALAN DAN STOK BERBASIS SMS GATEWAY (Information Technology and Telematics, 2015)
Abstrak :~~PT. Sarana Sentra Abadijaya Company is engaged in sale of printer, refill ink, and cartridges. To facilitate the recording and reporting of accurate and fast, then PT. Means Sentra Abadijaya require an application for recording transactions and sending sms as reporting. This research was conducted with several stages of design and implementation. The design is how to make an application to integrate with sms gateway sales, while the implementation of this application for PT. Sarana Sentra Abadijaya Based on the results of testing applications for sales and stock information on PT. Sarana Sentra Abadijaya (Acaciana) is an application of the sale comes with sending sms which contains total sales, number of items sold, and the rest of the stock. Keywords : ~~sales, sms, sms gateway